Dominica : Poverty Reduction Strategy Paper; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report, 2006)
The Growth and Social Protection Strategy (GSPS) attaches great importance to the promotion of economic growth and job creation, given the nature of poverty in Dominica. The GSPS also stresses that existing health and education programs are essential to foster growth in the medium and long terms, but further efforts are needed. The GSPS contains a macroeconomic framework that is consistent with the proposed objectives of poverty reduction. The growth and fiscal targets envisaged in the macroeconomic framework are also consistent with the objective of maintaining public debt sustainability.